THE INFLUENCE OF UNDERPRICING OF SHARES IN COMPANIES THAT CONDUCT AN INITIAL PUBLIC OFFERING - Bayu Eko Saputro; Siti Hayati Efi Friantin; Yenni Khristiana (STIE AUB Surakarta, 2018)
The purpose of this study is to determine the influence of underwriters, auditor reputation, return on equity, debt to asset ratio and proceeds against underpricing of shares in companies conducting an initial public offering on the Indonesia Stock Exchange with observation period 2013-2016. Population in this research is company which do IPO year 2013-2016. The sample technique used is purposive sampling so that the number of companies as much as 84 companies with a total sample of 64 samples with sample criteria. This research is a quantitative research with secondary data in the form of financial statement and company prospectus. Data of this research are analyzed by descriptive statistic test, liniearity test and hypothesis test. The method of analysis used is multiple linear regression. The result of the analysis shows that the underwriter variable has an effect on the underpricing of stock, while the auditor's reputation variable, return on equity, debt to asset ratio and proceeds have no effect on underpricing of stock. Keywords : underwriter, auditor reputation, return on equity, debt to asset ratio, proceeds, underpricing